A REPRESENTAÇÃO DA POBREZA NOS REGISTROS DE REPRESSÃO: METODOLOGIA DO TRABALHO COM FONTES CRIMINAIS (Revista de História Regional, 2007)
In this article I discuss the sources that proceeds from the repressions archives. Based on these documentation, I search for to perceive the link betwen poverty and vagrancy, verifying the instituted inquests against the poor and unemployed men in the city of São Paulo, by the years 1933 to 1942.